2012
DOI: 10.5935/0101-2800.20120025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two hand hygiene techniques in peritoneal dialysis patients

Abstract: Hand rubbing with gel-alcohol was more effective in reducing the number of colonies recovered than the other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…A study comparing the two HH techniques in peritoneal dialysis patients demonstrated that sanitation with alcohol preparation produced a greater reduction in the number of colony forming units when compared to a non-antimicrobial soap (33) .…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing the two HH techniques in peritoneal dialysis patients demonstrated that sanitation with alcohol preparation produced a greater reduction in the number of colony forming units when compared to a non-antimicrobial soap (33) .…”
Section: Discussionmentioning
confidence: 99%
“…It was determined in the present study that almost all of the patients obeyed the general hygiene rules, but most of them did not wear a mask during the procedure (Table 3). When examining the published studies about following the general hygiene rules, primarily studies on hand washing have been found [17,18]. It was determined in the present study that 14.0% of those undergoing peritoneal dialysis did not wash their hands before the dialysis.…”
Section: Discussionmentioning
confidence: 71%
“…The sequence of HH was not randomized. Colonization by CNS before HH was evaluated in a previous study (19). Different species of CNS were not evaluated, and despite the reduction of CNS colonization with AHH, changes in hand flora leading to more pathogenic strains of CNS cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Peritonitis is a serious complication of PD therapy and a major cause of technique failure and death. Worldwide, gram-positive cocci have been the main agents of bacterial peritonitis, CNS being the more frequently identified micro-organism (3)(4)(5)(6)(7)19,(29)(30)(31)(32). Despite being responsible for only a small proportion of peritonitis episodes in many countries, S. aureus has been the main agent of PD peritonitis in some Latin American countries, particularly Brazil (6,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation